Entrepreneurship in Germany and the role of the new self‐employed - Gruner, Herbert (Journal of Business Economics and Management, 2006)
In the following article we show the meaning of entrepreneurship and self employment for the German economy after the reunification. We flashlight the German founding boom since 2003, as new labour market policy instruments have been developed and financed. On the basis of three regional investigations we compared the new self‐employed according to: social and vocational‐biographical development, motivation and nature of business founded, founding qualifications and qualification strategies. First published online: 14 Oct 2010